Electrical Installation and Calculation Analysist of Roll Bending Machine Drive System - Susilawati Susilawati; Muhammad Fahmi; Agus Haris Abadi (VANOS Journal of Mechanical Engineering Education, 2020)
Bending and rolling service providers in Subang Regency are still minimal, based on observation data in five workshops, there is only one workshop that provides bending and rolling services, in addition, in the manufacture of the bending roll machine, it is necessary to have an electrical installation as the power that drives the drive system and analysis of the calculation of the drive system as planning to determine and install the drive system to be used. This final project is a qualitative descriptive study with the stage of data collection, wiring diagrams and calculations, installation, testing, and analysis.  The results of the study can be concluded that: (1) the electrical installation uses two main components including a 1 phase 1.5 HP electric motor and a 15 A cam starter 3, (2) the analysis of the calculation of the drive system includes the calculation of the power of the motor drive with the results: driving torque = 269 , 66 Nm, Driven torque = 210.66 Nm, calculation of the final rotation ratio of the roller with the results: the final rotation ratio n3 = 39.94 rpm, chain calculation ratio with chain speed results: v = 0.15 m / s, the amount of chain workload = 88 kg, comparison of theoretical calculations with technical calculations (measured tests) which include electric motors: (1400 rpm): (1403 rpm) difference = 3 rpm, speed reducer = (46.6 rpm): (59.93 rpm) difference = 13.33 rpm, main shaft sprocket = (39.94 rpm):(32, 83) difference = 7.11 rpm.